Effect of preceding rabi crops on yield of succeeding Deshi and Tossa jute (Bangladesh Agronomy Journal, 2015)
An experiment was conducted at the Jute Research Regional Station, Kishoreganj of Bangladesh Jute Research Institute, during 2001-2002 and 2002-2003 to find out the effects of preceding crops, viz. wheat, potato, lentil, and fallow on yield of succeeding jute crops. The experiment was laid out in a randomized complete block design with four replications. The results revealed that plant height and base diameter of CVL-1 and O-9897 were not affected significantly by the preceding rabi crops. The fibre and stick yields of both the jute varieties were affected significantly. The highest fibre yield of CVL-1 (3.90 t ha-1 and 3.77 t ha-1) and O-9897 (3.51 t ha-1 and 2.93 t ha-1) was recorded when those were grown after potato and the yield was the lowest when grown after wheat and fallow land in both the years. There was no sharp variation in harvest index, which showed inconsistent between the years.Bangladesh Agron. J. 2014, 17(2): 15-19